2022
DOI: 10.3390/healthcare10081439
|View full text |Cite
|
Sign up to set email alerts
|

Mental Wellbeing of Indonesian Students: Mean Comparison with UK Students and Relationships with Self-Compassion and Academic Engagement

Abstract: The number of Indonesian students in higher education has been increasing rapidly. However, many Indonesian university students report experiencing mental distress. Research on student wellbeing found that self-compassion (i.e., being kind towards oneself in challenging times) and academic engagement (i.e., a commitment and purposeful effort toward study) are essential to students’ mental wellbeing. With the present study, we aimed to assess the mental wellbeing of Indonesian students. A convenience sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 69 publications
2
8
0
2
Order By: Relevance
“…The positive association of mental well-being and intrinsic motivation in Czech students supports SDT as an explanatory theoretical model. Extending previous findings in Asia and Africa [ 46 , 58 ], the present study showed the applicability of SDT to non-WEIRD cultures that are located in Europe.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The positive association of mental well-being and intrinsic motivation in Czech students supports SDT as an explanatory theoretical model. Extending previous findings in Asia and Africa [ 46 , 58 ], the present study showed the applicability of SDT to non-WEIRD cultures that are located in Europe.…”
Section: Discussionsupporting
confidence: 85%
“…What is not yet established, however, is how self-reassurance and intrinsic motivation interact to influence mental well-being. As findings in university students of different cultures indicate self-compassion to have positive association with intrinsic motivation [ 44 , 45 , 46 , 47 , 48 ], it is hypothesised in this study that intrinsic motivation may mediate the relationship between self-compassion and mental well-being in Czech students. Because interventions to increase self-compassion in students have provided evidence of enduring mental well-being effects up to six months following intervention [ 49 ], self-compassion has promise as an ability that can be developed for Czech students.…”
Section: Introductionmentioning
confidence: 86%
“…Several studies have shown the mental wellbeing of Indonesian higher education students is lower than those in other countries. Of Indonesian HE students, between 37–53% have reported high stress symptoms, with 51% feeling anxiety and 25% experiencing depression [ 6 ]. In Indonesia, there is both a lack of HE mental health services and an underutilisation of the existing services [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini menjadikan tingkat stress pada usia remaja menjadi lebih tinggi berdasarkan (Kotera et al, 2022) yang menyatakan bahwa seiring dengan peningkatan jumlah siswa-siswi atau mahasiswa di akademik Indonesia, semakin tinggi juga jumlah siswa yang memiliki kesehatan mental yang buruk. Kesehatan mental pada remaja banyak jenisnya tetapi masalah pada remaja salah satu yang sering terjadi adalah stress yang tidak terkontrol.…”
Section: Latar Belakangunclassified